PENGARUH PENAMBAHAN SERAT POLYPROPYLENE TERHADAP KUAT TEKAN BETON DENGAN AGREGAT KASAR BETON BEKAS - Wibowo, Rendi Gusta; Rohman, Rosyid Kholilur; Suweno, Hery (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Concrete is the most widely used construction material, but the continued use of natural aggregates has led to increased exploitation of natural resources. The use of recycled concrete aggregate (RCA) is an alternative to support the concept of sustainable construction. On the other hand, the addition of polypropylene fiber (PPF) is known to improve crack resistance and mechanical properties of concrete. This study aims to determine the effect of variations in polypropylene fiber (PPF) on the compressive strength of concrete with recycled concrete coarse aggregate. The proportion of recycled concrete aggregate is 50% of natural aggregate. The fiber variations used are 0%, 0.25%, 0.5%, 0.75%, and 1% of the concrete volume. Cylindrical test specimens were tested according to SNI standards. The results showed that the addition of fiber reduced the slump value, from 96 mm (0%) to 78 mm (1%). Compressive strength increased with increasing proportion of polypropylene fiber. The optimum content was at 0.5% polypropylene fiber, which provided the most effective strength increase. The use of RCA as a coarse aggregate remains feasible, and the addition of polypropylene fiber has been shown to increase the compressive strength of concrete so that it can be used in structural work.